Web-Based Triage Analysis (Triage Go) on Speed and Accuracy of Service - Ramliana, Adhy; Triyanto, Endang (GLOBAL HEALTH SCIENCE GROUP, 2025)
The increasing number of visits to the ER requires nurses and ER staff to move quickly in assessing the condition and sorting patients based on their severity. This is to determine the priority of patient management. The administrative process for registration often takes a long time so that nurses still use paper to perform initial triage on patients. In this digital era, technology-based solutions are becoming increasingly relevant, especially with the increasing use of digital platforms worldwide. Method: Article search using electronic databases such as Pubmed, Science direct, and Google Scholar. The search for articles used were articles published in 2019-2024, using the keywords